Design Guidelines for Onboarding Experience in Narrative-rich Games - ZHANG, XINGYU; YIBIN, HUAI (My University, 2021)
The first minutes and hours of a game’s whole gameplay are called the onboarding phase. In this project we provided guidelines for designing the onboarding phases in narrative-rich games which contains abundant narration elements. The purpose of designing a such game’s onboarding phase is to increase players’ retention, to achieve this goal, the onboarding needs to provide players good sense of mastery, sense of purpose and sense of immersion. The guidelines were generated through firstperson research and empirical research. In the first-person research we conducted artifact analysis on 8 narrative-rich games for how they designed their onboarding phases, the result was analyzed through affinity diagrams into 10 themes. One of the games analyzed was selected for the empirical research, in which participants played the game’s onboarding and reflected on how the game influenced their experiences regarding sense of mastery, sense of purpose and sense of immersion, the result was documented and analyzed through thematic analysis. Motivated by the result from first-person research and the empirical research, we present 12 guidelines about how to design onboarding phases in narrative-rich games to increase players’ senses of mastery, senses of purpose and senses of immersion.
Keywords: Design Guidelines; The Onboarding Phase; Narrative-rich Games; First- Person Research; Empirical Research